Decision making in the evaluation, selection and implementation of ERP systems - Shakir, Maha (Massey University, 2000)
The evaluation, selection and implementation (ESI) of ERP systems involve making multiple decisions during the lifecycle of the ERP project. This study tries to map six models of decision-making to the ERP project lifecycle, which is conceptualized using case study data for a health service provider organization in New Zealand. ERP projects are deemed strategic projects for which success or failure has a great impact on the organization. Gaining an understanding of the decision-making process during the life of the project helps in better preparations and planning before and during each phase. Findings suggest that some decision-making models apply to the stages of evaluation, selection and implementation while others are missing. The three models that apply are the administrative, adaptive and political models. This study aids practitioners in better planning and implementation of ERP projects through better understanding the decision-making process. A benefit to academics is in providing new insights for ERP systems implementation, an area where little research is conducted.
Keywords: Enterprise resource planning (ERP); Decision-making